Codeswitching of bilingual preschoolers in Pakistan: A study of Arabic and Urdu alphabets - Shahid, Muhammad Ali; Mahmood, Anser (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Urdu is the official language of Pakistan, while Arabic is the language of the Holy Quran, Muslims' sacred book. Pakistan, as a Muslim country with a religious bond, makes it obligatory for Muslims to recognize and interpret Allah's commandments, as well as to pray and recite the Holy Quran. The most effective skill is oral communication. It has become one of the fundamental language learning skills, alongside listening, reading, and writing. Pronunciation is the process of processing speech sounds to communicate. The current research study focuses on the codeswitching of bilingual preschoolers while learning the Arabic and Urdu alphabets. The study demonstrates why preschool children fail to recognize images of simple words in Arabic and Urdu at the same time and how this challenge can be tackled with the ingenuity of a committed teacher. The researcher used the Oral Proficiency Test (OPT) to assess the quality of the children's pronunciation, and he processed the data using Setiyadi’s (2020) Triangulation of method, which includes three data collection techniques: observation, interview, and questionnaire. The observation focused on how the teacher pronounced both alphabets and how the children responded by pronouncing the same at the top of their voices to make good use of articulators. Later, an interview and a questionnaire were conducted to collect data that could be used to ensure the validity of the observational results. Creswell & Baez’s (2020) Model of the Structure of Study was implemented. The research on bilingual preschoolers is significant in that it reveals that the children had difficulty in discerning resembling sounds from the Arabic and Urdu alphabets and that this difficulty caused them to deviate from one alphabet to the other. Speech therapists, pathologists, psychologists, bilingual scholars, and researchers will all benefit from the research.